2009
DOI: 10.3858/emm.2009.41.5.037
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of epinephrine-induced gluconeogenesis in aging

Abstract: The effects of glucagon and epinephrine on gluconeogenesis in young (4 month) and old (24 month) Fisher 344 rat hepatocytes were compared. In contrast to glucagon, which had a similar effect on gluconeogenesis in both young and old cells, epinephrine caused a smaller increase in gluconeogenesis in old rat hepatocytes than in young hepatocytes. β 2 adrenergic receptor (β 2 -AR) expression slightly decreased in aged rat liver, and there were differences between young and old hepatocytes in their patterns of G pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…Alternatively, our data agree with reports of age-related alterations in G protein-coupled receptor kinases (GRKs) and β-arrestin expression and activity in liver, vascular smooth muscle and myocardial cells from F344 rats [Kim et al, 2009; Schutzer et al, 2005; Dobson et al, 2003]. Since GRKs, particularly, GRK-2, and β-arrestin are required for β 2 -AR desensitization through internalization and degradation, our observed increase in β-AR signaling despite increased SNA could also be explained by a deficiency of old splenocytes to internalize β-AR in response to higher NE concentrations.…”
Section: Discussionsupporting
confidence: 92%
“…Alternatively, our data agree with reports of age-related alterations in G protein-coupled receptor kinases (GRKs) and β-arrestin expression and activity in liver, vascular smooth muscle and myocardial cells from F344 rats [Kim et al, 2009; Schutzer et al, 2005; Dobson et al, 2003]. Since GRKs, particularly, GRK-2, and β-arrestin are required for β 2 -AR desensitization through internalization and degradation, our observed increase in β-AR signaling despite increased SNA could also be explained by a deficiency of old splenocytes to internalize β-AR in response to higher NE concentrations.…”
Section: Discussionsupporting
confidence: 92%
“…[19][20][21] Our results showed that the serum concentration of epinephrine increased in a dosedependent manner after the administration of olanzapine (Fig. 3B).…”
Section: Discussionmentioning
confidence: 61%
“…Serum concentrations of immunoreactive insulin and glucagon were 1,OLZ , the serum concentration of olanzapine in the central compartment; C 2,OLZ , the serum concentration of olanzapine in the peripheral compartment; V 1 , the distribution volume of olanzapine in the central compartment; k 12 , the first order transfer rate constant for a drug moving from the central to the peripheral compartment; k 21 , the first order transfer rate constant for a drug moving from the peripheral to the central compartment; V max,OLZ , the maximum velocity of the elimination of olanzapine; K m,OLZ , the Michaelis constant for the elimination of olanzapine; C Epi , the serum concentration of epinephrine; k in,Epi , the zero order constant for epinephrine input; C Epi(0) , the serum concentration of epinephrine at baseline; K S,Epi , the proportionality constant for the stimulation of epinephrine input by olanzapine; C Glu , the serum concentration of glucose; k in,Glu , the zero order constant for glucose input; C Glu(0) , the serum concentration of glucose at baseline; E max,Glu the maximum effect for the stimulation of glucose input by epinephrine; EC 50,Glu , the epinephrine concentration corresponding to 50% of the maximum effect for the stimulation of glucose input by epinephrine.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, GRK and β‐arrestin1 are altered in congestive heart failure (Vinge et al ., ), and GRK2/3 in the failing human heart (Ungerer et al ., ). Studies in other tissues support age‐dependent shifts in GRK expression: GRK2 and 6 (and β‐arrestin‐2) are suppressed with age in the human brain (Grange‐Midroit et al ., ); and age switches the liver isoform profile from GRK2 to GRK3 and down‐regulates β‐arrestin (Kim et al ., ). In contrast, in diabetic mice, hyperinsulinaemia up‐regulates GRK (and down‐regulates β‐arrestin2) in vascular smooth muscle, inhibiting activation of the Akt/eNOS pathway involved in cytoprotection in other cell types (Taguchi et al ., ).…”
Section: Sarcolemmal Makeup and Cardioprotective Signallingmentioning
confidence: 97%